Increasing Consumer Repurchase Intention through Scent Marketing and Brand Experience at Fore Coffee - Alfitri, Fazira Rizqy; Hidayat, M. Faiz Ali; Fahriza, Muhammad Rizqi (AKSIOMA : Jurnal Manajemen, 2026)
Changes in consumption patterns that emphasize emotional aspects and experiences have shifted marketing strategies from purely functional approaches to brand experience-based approaches. This research focuses on analyzing repurchase intensity at Fore Coffee Mall Solo Paragon, examining the extent to which scent marketing and customer impressions of the brand play a role in this process. Using a quantitative approach, data was obtained from 120 respondents who met the criteria determined by the purposive sampling method. The data was tested using SPSS. The analysis techniques applied included instrument testing, classical assumptions, multiple linear regression, t-test, and F-test. Based on the study findings, consumer repurchase interest is positively influenced by brand experience and aroma stimulation. This significant influence was proven to be consistent, both when the variables were tested partially and simultaneously. Scent marketing and brand experience were able to explain 60.7% of the repurchase intention variable, while 39.3% was influenced by other factors outside the research model.